Management of thyroid nodules in Department of Otolaryngology - W Sinkijcharoenchai; K Pruegsanusak; K Jantharapattana (Journal of Health Science and Medical Research (JHSMR), 2005)
Objective: To review demographic data, preoperative laboratory results, postoperative pathologic results of patients with thyroid nodules in Department of Otolaryngology, Songklanagarind Hospital. Material and Methods: The records of patients with thyroid nodules in Department of Otolaryngology from 1999 to 2003 were reviewed to evaluate preoperative laboratory results and postoperative pathologic results. Results: There were 393 patients, 334 females and 59 males. Age ranged from 41 to 50 years. The preoperative laboratory tests (thyroid function test, ultrasound, thyroid scan and/or fine needle aspiration biopsy) of these patients were reviewed and compared to the postoperative pathologic reports. From the thyroid function test results, 88.6% (226/255) of patients were euthyroid while hypothyroidism was found in Hashimoto's thyroiditis (11/16) and hyperthyroidism in toxic nodular goiter  (10/13). From the ultrasound results, the prevalence of solitary nodule was the same as that of multiple nodules but solitary nodules were more likely to be malignant than were multinodular goiter, 33.3% (7/21) and 9.5% (2/21) respectively. From the thyroid scan results, most nodules were cold nodules 75% (12/16), and warm and cold nodules were more likely to be malignant than hot nodules. From the FNAB results, most nodules were found to be benign 49.8% (129/259), followed by follicular lesion 31.6% (82/259), suspicious for malignancy 9.6% (25/259) and malignant 8.8% (23/259). The analysis of FNAB in this study revealed a sensitivity of 75.6% (95% CI = 62.2-86.7), specificity of 89.4% (95% CI = 84.1-94.7). Conclusion: FNAB is the most valid test to distinguish benign from malignant thyroid nodules when compared to other preoperative tests, so it should be used as an initial diagnostic test for those who have thyroid nodules. The thyroid function test and thyroid scan are used to confirm the functional status of thyroid nodules and the ultrasonography is recommended to determine the nodules' size during follow up and as a guide for FNAB localization.